Stereoselective Synthesis of syn-γ-Hydroxynorvaline and Related α-Amino Acids - Valachová, Dominika; Ferko, Branislav; Puchľová, Eva; Caletková, Oľga; Berkeš, Dušan; Kolarovič, Andrej; Jakubec, Pavol (Synthesis, 2019)
The total syntheses of three enantiomerically pure non-proteinogenic amino acids, l-norvaline, γ-oxonorvaline, and syn-γ-hydroxynorvaline, are reported. The chromatography-free route pivoted on the construction of highly enantiomerically enriched substituted α-amino-γ-oxopentanoic acid, from which all three members were accessed divergently via chemoselective and stereoselective reductions. The rapid synthesis of this key α-amino-γ-oxopentanoic acid was achieved by a highly diastereoselective crystallisation-driven three-component Mannich reaction from the readily available building blocks acetone, glyoxylic acid monohydrate, and (S)-(4-methoxyphenyl)ethylamine. The enantiomeric purity of all target molecules was confirmed by HPLC analysis, either of the amino acids or their derivatives.
Keywords: stereoselective synthesis; α-amino acids; Mannich reaction; crystallisation-induced; norvaline; γ-hydroxynorvaline; aza-Michael addition